IMBT (Ijarah Mumtahiya Bittamlik) as the main contract in mortgage (Home Ownership Credit) - Wahyudhi, Imam; Irawan, Agus Wahyu; Khoir, Misbahul (Universitas Islam Lamongan, 2024)
The non-compliance of the Ijarah Mumtahiya Bit-Tamlik (IMBT) contract as the main contract in mortgages (Home Ownership Credit) with the DSN-MUI fatwa in its implementation procedures is a problem in the Ijarah Mumtahiya Bit-Tamlik (IMBT) contract. In this study, the research method used is Library Research, where secondary data is obtained from data provided by data providers from several Islamic banks and offline data from several books. The results of this discussion show that according to DSN-MUI fatwa Number 27 (2002), Ijarah Mumtahiya Bit-Tamlik (IMBT) is a form of lease agreement for goods or services that includes an option to transfer ownership rights of the leased object to the lessee when the lease period ends. In general, in Islamic banks, in the mortgage financing scheme with the Ijarah Mumtahiya Bit-Tamlik (IMBT) contract, the bank will purchase an asset and then lease-sell the asset to the customer. The implementation of the Ijarah Mumtahiya Bit-Tamlik (IMBT) contract must comply with DSN-MUI fatwa Number 27 (2002) concerning Ijarah Mumtahiya Bit-Tamlik (IMBT), which states that the transfer of ownership, either by sale or gift, is carried out after the ijarah period ends